2021
DOI: 10.1002/wcs.1577
|View full text |Cite
|
Sign up to set email alerts
|

Context and attention control determine whether attending to competing information helps or hinders learning in school‐aged children

Abstract: Attention control regulates efficient processing of goal‐relevant information by suppressing interference from irrelevant competing inputs while also flexibly allocating attention across relevant inputs according to task demands. Research has established that developing attention control skills promote effective learning by minimizing distractions from task‐irrelevant competing information. Additional research also suggests that competing contextual information can provide meaningful input for learning and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…Adult studies show that memory‐guided attention is more likely to be engaged in natural than artificial scenes and in testing contexts that necessitate head and eye movements (Võ & Wolfe, 2012, 2015). In infants, complex scene structures might pose a different challenge: The richness and complexity of the natural scene structure could have been too distracting for infants to efficiently learn coherent item‐in‐context associations and use memory‐guided attention (Markant & Amso, 2022). However, 8‐month‐old infants indeed became faster to detect targets presented in repeated contexts even in our more complex scenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult studies show that memory‐guided attention is more likely to be engaged in natural than artificial scenes and in testing contexts that necessitate head and eye movements (Võ & Wolfe, 2012, 2015). In infants, complex scene structures might pose a different challenge: The richness and complexity of the natural scene structure could have been too distracting for infants to efficiently learn coherent item‐in‐context associations and use memory‐guided attention (Markant & Amso, 2022). However, 8‐month‐old infants indeed became faster to detect targets presented in repeated contexts even in our more complex scenes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, infant dynamics between attention and memory engagement may differ from those of adults and require their own empirical consideration. The richness and complexity of natural scenes will often be correlated with the number of distracting elements, which may render infants less able to process the target‐in‐scene pairings and thus less likely to benefit from contextual repetition (Markant & Amso, 2022). In such a case, infants may default to a de novo search strategy on each trial, rather than one that uses visuospatial context to guide target visual search.…”
Section: Introductionmentioning
confidence: 99%
“…Across these conditions, the visual experiences are identical, but the demands on feature integration are quite different. For example, detecting a target object (e.g., black circle) that is also defined by a feature that is irrelevant to the selection goal (e.g., motion) may place a greater demand on attentional resources than detecting a target object containing only a single relevant feature (e.g., color), simply because the irrelevant feature may be incidentally integrated with the object's other features (Prediction 3; Markant & Amso, 2022). Moreover, detecting a conjunction of features (e.g., luminance‐motion) may be more costly than a detecting a single feature (e.g., luminance only) regardless of the additional cost of distraction incurred by irrelevant features (e.g., motion; Prediction 4).…”
Section: The Development Of Visual Feature Processing Competence Acro...mentioning
confidence: 99%
“…The ability to selectively attend to visual information that is relevant for a behavioral goal while ignoring competing irrelevant information improves across infancy, through childhood, and into adolescence (Hendry et al, 2019;Plude et al, 1994). This developmental change in visual selective attention ability in turn supports learning and memory at a time when children transition to formal schooling and are expected to acquire immense amounts of knowledge (Markant & Amso, 2022;Merkley et al, 2018;Stevens & Bavelier, 2012). Indeed, children's visual selective attention is challenged by classrooms full of colorful artwork, posters, and talkative peers, and their academic success hinges on their ability to focus their attention on the teacher and lesson while ignoring these distractions, especially for neurodiverse children (Fisher et al, 2014;Hanley et al, 2017).…”
mentioning
confidence: 96%
“…Attentional control refers to the ability to select target-related information while suppressing information not related to the subject to be learned. Studies have revealed that the development of attentional control skills supports effective learning by minimizing distractions from competing information irrelevant to the task (Markant and Amso, 2022).…”
Section: Introductionmentioning
confidence: 99%